Anti-TGF-β Antibody, 1D11, Ameliorates Glomerular Fibrosis in Mouse Models after the Onset of Proteinuria. - Xiaoyan Liang; H William Schnaper; Taiji Matsusaka; Ira Pastan; Steve Ledbetter; Tomoko Hayashida (PLoS ONE)
Fibrosis is a final common pathway leading to loss of kidney function, in which the fibrogenic cytokine, transforming growth factor β (TGF-β), plays a central role. While previous studies showed that TGF-β antagonism by various means prevents fibrosis in mouse models, clinical approaches based on these findings remain elusive. 1D11 is a neutralizing antibody to all three isoforms of TGF-β. In both adriamycin (ADR)-induced nephropathy and NEP25 podocyte ablation nephropathy, thrice-weekly intraperitoneal administration of 1D11 from the day of disease induction until the mice were sacrificed (day 14 for ADR and day 28 for NEP25), significantly reduced glomerular COL1A2 mRNA accumulation and histological changes. Consistent with our previous findings, proteinuria remained overt in the mice treated with 1D11, suggesting distinct mechanisms for proteinuria and fibrogenesis. Podocyte numbers determined by WT1 staining were significantly reduced in NEP25-model glomeruli as expected, while WT1-positive cells were preserved in mice receiving 1D11. Even when 1D11 was administered after the onset of proteinuria on day 3, 1D11 preserved WT1-positive cell numbers in glomeruli and significantly reduced glomerular scar score (2.5 ± 0.2 [control IgG] vs. 1.8 ± 0.2 [1D11], P < 0.05) and glomerular COL1A2 mRNA expression (19.3 ± 4.4 [control IgG] vs. 8.4 ± 2.4 [1D11] fold increase over the healthy control, P < 0.05). Transmission electron microscopy revealed loss of podocytes and denuded glomerular basement membrane in NEP25 mice with disease, whereas podocytes remained attached to the basement membrane, though effaced and swollen, in those receiving 1D11 from day 3. Together, these data suggest that TGF-β neutralization by 1D11 prevents glomerular fibrosis even when started after the onset of proteinuria. While overt proteinuria and podocyte effacement persist, 1D11 prevents total podocytes detachment, which might be a key event activating fibrogenic events in glomeruli.